2016
DOI: 10.1557/adv.2016.642
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of simulant ‘lava-like’ fuel containing materials (LFCM) from the Chernobyl reactor Unit 4 meltdown

Abstract: A preliminary investigation of the synthesis and characterization of simulant ‘lava-like’ fuel containing materials (LFCM), as low activity analogues of LFCM produced by the melt down of Chernobyl Unit 4. Simulant materials were synthesized by melting batched reagents in a tube furnace at 1500 °C, under reducing atmosphere with controlled cooling to room temperature, to simulate conditions of lava formation. Characterization using XRD and SEM-EDX identified several crystalline phases including ZrO2, UOx and so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 6 publications
(8 reference statements)
0
12
0
Order By: Relevance
“…Brown LFCM contained more zircon than black LFCM, 12 and contained larger crystallites, indicating that zircon formation was more favourable in the former composition. Analysis of the local coordination of U in the glass matrix found that in simulant brown LFCM, U was present in a U(IV)O 6 -type environment, while in the simulant black LFCM it was in a UO 8 -type environment, similar to the coordination in coffinite, the U-end member of the U-zircon solid solution (Zr 1Àx U x SiO 4 ).…”
Section: Insights To the Paragenesis Of Simulant Chernobyl Lfcmmentioning
confidence: 94%
See 3 more Smart Citations
“…Brown LFCM contained more zircon than black LFCM, 12 and contained larger crystallites, indicating that zircon formation was more favourable in the former composition. Analysis of the local coordination of U in the glass matrix found that in simulant brown LFCM, U was present in a U(IV)O 6 -type environment, while in the simulant black LFCM it was in a UO 8 -type environment, similar to the coordination in coffinite, the U-end member of the U-zircon solid solution (Zr 1Àx U x SiO 4 ).…”
Section: Insights To the Paragenesis Of Simulant Chernobyl Lfcmmentioning
confidence: 94%
“…Such zoning is attributed to differential growth rates of crystal faces during cooling. 38 Previous analysis of the simulant brown LFCM showed very faint zoning throughout the crystallite, 12 however, only two zones were apparent in the m-XAS analysis. Since the temperature of U-rich zircon formation in this simulant material was found to be similar to chernobylite in real LFCM (crystallites were formed at $1245 AE 5 C and estimates made from analysis of real LFCM gave a range of between 1000-1250 C), 13,37 the differences observed between the simulant and real samples are most likely due to differences in the cooling regime.…”
Section: Insights To the Paragenesis Of Simulant Chernobyl Lfcmmentioning
confidence: 96%
See 2 more Smart Citations
“…To overcome this lack of information, past attempts to simulate lowactivity LFCMs (i.e., containing no fission products, only depleted uranium) have been made to help understand the conditions within the reactor during the accident, however, this work was unable to accurately approximate the microstructure, morphology and mineralogy of LFCM. [19][20][21][22] One important aspect of LFCM behaviour that has not yet been investigated in detail is its corrosion behaviour within the reactor building. It is known that, due to the condensation of water inside the roof of the original Chernobyl sarcophagus (as a result of the temperature differential within and outside the structure), and the presence of holes in the sarcophagus roof, a significant proportion of water has dripped onto the LFCM causing it to corrode.…”
Section: Introductionmentioning
confidence: 99%